Implementasi transformasi digital dalam pengajuan piagam Musholla/Masjid melalui aplikasi PTSP di Bagian Bimas Kementerian Agama Kabupaten Malang - Alfiatin, Lisa Nur Alif (Maliki Interdisciplinary Journal, 2024)
This study examines the implementation of digital transformation in the process of applying for musholla and mosque certificates through the One-Stop Integrated Service (PTSP) Application in the Islamic Community Guidance (BIMAS) section of the Ministry of Religious Affairs in Malang Regency. Digital transformation in the public sector aims to enhance the efficiency, effectiveness, transparency, and accountability of public services. PTSP is an initiative that integrates various services into one digital platform, allowing the public to access services more easily and quickly. This study uses a qualitative descriptive approach to describe the changes that occurred before and after the implementation of PTSP. The research findings show that the PTSP application successfully improved administrative process efficiency, expedited the certificate application process, and increased transparency and accountability of services. Despite challenges such as limited internet access and low digital literacy, digital transformation through PTSP provides many benefits for the public and the Ministry of Religious Affairs in Malang Regency.